2022
DOI: 10.17576/gema-2022-2201-13
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Online Advice-Seeking Strategies between Malaysian and Australian Women

Abstract: Advice discourse is common in our everyday life. As such, research on advice is diverse and covers advice-related communicative practices such as advice-seeking, advice-giving and reception to advice. Past research on advice has also examined various factors affecting advicerelated practices such as the relationship between advice and politeness, gender, and characteristics of interlocutors. Although advice is a much-researched area, comparative studies that attempt to compare advice-seeking strategies in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…It was also observed that some patients used more than one type of WH question, and they sometimes used yes/no questions with them. This finding is in line with Kouper’s (2010) study, which showed that one message often contains several questions and supports the findings of Pung (2017) . Another thing to note is that doctors sometimes do not respond to yes/no questions with yes/no answers, as they also use clarifications.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was also observed that some patients used more than one type of WH question, and they sometimes used yes/no questions with them. This finding is in line with Kouper’s (2010) study, which showed that one message often contains several questions and supports the findings of Pung (2017) . Another thing to note is that doctors sometimes do not respond to yes/no questions with yes/no answers, as they also use clarifications.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have been conducted to investigate the speech act of giving health advice in different contexts, including radio advice programs ( DeCapua and Dunham, 1993 ), TV health programs ( Ahmed and Ahmed, 2019 ), Twitter ( El-Dakhs, 2021 ), and online forums ( Morrow, 2006 ; Kouper, 2010 ; Locher, 2013 ; Pung, 2017 ; Bates, 2021 ). For example, in the context of radio advice programs, DeCapua and Dunham (1993) examined the patterns in American English used by speakers (adults) when requesting and giving advice.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of online advice are increasingly common, covering issues as diverse as legal matters [25], health conditions [26], or job-seeking [27], as well as information on animal welfare such as searches for specific diseases of pets [28]. Research methods include broad internet searches [26], studies of exchanges on social media pages or in online forums [29], and experimental designs [27,30]. There is evidence of cultural differences in how people search for or ask questions on social media [29], as well as varying willingness to act on advice based on the nature of that advice or its source [31].…”
Section: Introductionmentioning
confidence: 99%
“…Research methods include broad internet searches [26], studies of exchanges on social media pages or in online forums [29], and experimental designs [27,30]. There is evidence of cultural differences in how people search for or ask questions on social media [29], as well as varying willingness to act on advice based on the nature of that advice or its source [31]. Therefore, it is important to document the source of the advice, its nature, and any evidence of cultural or regional influence.…”
Section: Introductionmentioning
confidence: 99%